Arduino prototyping techniques : building and testing your ideas (O'Reilly, 2017)
"You've created your first prototypes using the Arduino micro-controller, you understand how to input to it, output from it, and now you're ready for more. Maybe you even want to commercialize your prototype. This course transforms your Arduino prototypes from basic to advanced, presenting a new set of skills, techniques, and technologies you can use to make your prototypes more useful, robust, and perhaps, market ready."--Resource description page.